2000
DOI: 10.1080/00032710008543205
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Determination of Chlorzoxazone in pure State and Formulations Through Oxidative Coupling of its Hydrolysis Product

Abstract: Three simple and sensitive procedures (Methods A, B and C) for the assay of chlorzoxazone (CZZ) in pure form and in formulations are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…2,3 Various analytical methods for therapeutic monitoring have been reported in the literature for the determination of Chlorzoxazone in commercial dosage form and biological fluids such as high-performance liquid chromatography (HPLC), 4 reverse phaseÀhigh performance liquid chromatography (RP-HPLC), 5 liquid chromatography electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS), 6 and spectrophotometry. 7 The main problems encountered in using such methods are either the need for derivatization or the need for time-consuming extraction procedures.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Various analytical methods for therapeutic monitoring have been reported in the literature for the determination of Chlorzoxazone in commercial dosage form and biological fluids such as high-performance liquid chromatography (HPLC), 4 reverse phaseÀhigh performance liquid chromatography (RP-HPLC), 5 liquid chromatography electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS), 6 and spectrophotometry. 7 The main problems encountered in using such methods are either the need for derivatization or the need for time-consuming extraction procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The linear range and limit of detection of the proposed method were also compared with the previously reported methods (Table 2). It is observed that the detection limit was better than in the reported HPLC method, 3 and the lower linear range was lower than in the published HPLC methods, 3,4,7,10 spectrophotometric methods, 24,32,33 capillary zone electrophoresis, 37 and the voltammetric method using the gold electrode. 39…”
Section: Analytical Performance Of the Proposed Methodsmentioning
confidence: 76%
“…It is used as an adjunct in the symptomatic treatment of painful muscle spasm. 1,2 phy, [3][4][5][6][7][8][9][10][11][12][13] thin layer chromatography, [14][15][16][17] liquid chromatography-tandem mass spectrometry, 18 packed column supercritical fluid chromatography, [19][20] gas chromatography, [21][22][23] spectrophotometry, [24][25][26][27][28][29][30][31][32][33][34][35] fluorimetry, 36 and capillary zone electrophoresis. 37 Two papers have been described in literature concerning the voltammetric determination of chlorzoxazone based on the oxidation of the drug at the glassy carbon electrode and gold electrode.…”
Section: Introductionmentioning
confidence: 99%
“…These methods were applied for the analysis of this compound as a related substance of chlorzoxazone or as an environmental water pollutant. Few colorimetric methods were described for the determination of ACP through coupling with diazotized sulfanilic acid 7 or through oxidative coupling with 3-methyl-2-benzothia zolinone hydrazone (MBTH) in the presence of Fe(III), N, N-dimethyl-p-phenylene diamine (DMPD) in the presence of periodate (IO 4 -), or 2, 6dichloroquinone chlorimide (DCQC) 8 . Fluorometric determination of ACP was investigated by Stewart and Chan 9 based on chemical derivatization of ACP with fluorescamine at pH 4.2 and measuring the fluorescence at 495 nm after excitation at 395 nm.…”
Section: Chlorzoxazonementioning
confidence: 99%